(untitled) (Bangladesh Journal of Botany, 2021)
A highly cellulolytic actinomycete SR1 was locally isolated from rice straw and provisionally identified as Thermomonospora viridis. Optimum pH, temperature, carbon and nitrogen sources for its cellulase production were 6.5, 35°C, Carboxymethyl cellulase (CMC) and yeast extract, respectively whereas those of cellulase activity were 7.5, 40°C, CMC and peptone respectively. The effects of various metal ions and different reductant and inhibitors on its cellulase activity were investigated. Univalent Ag+ was found to decrease the enzyme activity whereas increased by bivalent Mg2+. Ethylene diamine tetraacetic acid (EDTA) caused remarkable decrease of cellulase activity but β-Mercaptoethanol stimulated its cellulase activity. Bangladesh J. Bot. 50(2): 395-404, 2021 (June)